2013
DOI: 10.1136/archdischild-2012-303558
|View full text |Cite
|
Sign up to set email alerts
|

Rapid home-based weaning of small children with feeding tube dependency: positive effects on feeding behaviour without deceleration of growth

Abstract: This rapid weaning programme for children with feeding tube dependency (FTD) improved the feeding behaviour and was associated with constant growth velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 14 publications
4
51
0
Order By: Relevance
“…The transition from tube to oral feeding (weaning) may take only several days or weeks, but in others, it can be very challenging, lasting months to years [2, 18, 28, 39]. Since weaning can be very difficult, it is best accomplished with a multidisciplinary approach, including health care workers in the field of pediatrics, dietetics, psychology, speech-language pathology, and/or occupational therapy [15, 31, 38].…”
Section: Tube Weaning Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition from tube to oral feeding (weaning) may take only several days or weeks, but in others, it can be very challenging, lasting months to years [2, 18, 28, 39]. Since weaning can be very difficult, it is best accomplished with a multidisciplinary approach, including health care workers in the field of pediatrics, dietetics, psychology, speech-language pathology, and/or occupational therapy [15, 31, 38].…”
Section: Tube Weaning Methodsmentioning
confidence: 99%
“…Several studies use reducing or discontinuing tube feeding for appetite stimulation as a weaning method [4, 7, 20, 21, 39]. Various hunger-inducing weaning programs exist internationally, which may be home based [26, 38] or clinical [4, 7, 20].…”
Section: Tube Weaning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] There were no long-term differences in BMI before entering the program compared to the follow-up. 10 The initial weight loss did not have a negative impact on the growth of children who transitioned from tube to oral feeding.…”
Section: Impact On Weight Gain and Growthmentioning
confidence: 87%
“…27 In 2 studies, the frequency of the FTD symptoms were addressed. 9,10 Both the studies showed a significant decrease in the FTD symptoms from entering the program to the follow-up. They also reported a significantly improved eating behavior, significant decrease of the FTD symptoms, and significant reduction of supplemental feeding via tube.…”
Section: Impact On Eating Behaviormentioning
confidence: 96%